Therapeutic potential of Triptolide in inhibiting breast cancer-induced bone destruction – PTHrP as a therapeutic target - Di, Wu; Minghan, Li; Zining, Huang; Chunshi, Zhou; Xiangyu, Hu; Zidong, Wang; Gang, Wu (Frontiers in Pharmacology, 2025)
IntroductionBone metastases are a common and severe complication in advanced breast cancer, affecting approximately 65% to 70% of patients and significantly reducing survival time. Osteolytic bone metastases, in particular, are challenging to manage due to their association with skeletal-related events (SREs) that accelerate disease progression and diminish the quality of life. These metastases are driven by a complex interaction between breast cancer cells and the bone microenvironment, leading to increased osteoclast activity and bone destruction. Current treatments, such as bisphosphonates, primarily aim to inhibit osteoclast function but are associated with serious side effects, underscoring the need for alternative therapies. Triptolide (TP), a bioactive compound derived from the traditional Chinese medicinal herb Tripterygium wilfordii Hook F. (TwHF), has demonstrated potent anti-tumor and anti-inflammatory properties, especially in abnormal bone remodeling disorders. This study aims to investigate the therapeutic potential of TP in treating breast cancer-induced bone metastases by examining its effects on osteoclastogenesis and tumor–bone microenvironment interactions.MethodsMouse bone marrow cells, RAW264.7 pre-osteoclasts and MC3T3‐E1 pre-osteoblasts were cultured with MDA‐MB-231 breast cancer cells or their conditioned medium to replicate the tumor microenvironment. Osteoclast formation was assessed via TRAP staining. Translational and transcriptional expression of key signaling molecules and related markers were determined using western blot and RT‐PCR. Binding interactions between TP and parathyroid hormone-related protein (PTHrP) were analyzed using microscale thermophoresis and molecular docking.ResultsTP treatment significantly reduced osteoclastogenesis in both co‐culture and conditioned medium systems. Our findings suggest that TP inhibits NF-κB and ERK signaling pathways, reduces breast cancer-induced osteoclastogenesis, and decreases NFATc1, CTSK, and RANKL expression. Molecular assays revealed a direct binding affinity between TP and PTHrP, suggesting TP interferes with PTHrP‐mediated signaling that promotes osteoclast activity.DiscussionThis study demonstrates that Triptolide effectively inhibits breast cancer‐induced osteolytic bone metastasis by suppressing key osteoclastogenic signaling pathways and modulating the tumor-bone microenvironment. We provide the first evidence of a direct interaction between TP and PTHrP, suggesting a novel mechanism through which TP may disrupt PTHrP-mediated osteoclast activation. These findings position TP as a promising alternative to current anti‐resorptive therapies for managing breast cancer-associated bone metastases.